When Depression Breeds Rejection Rather Than Compassion: Disagreeableness, Stigma, and Lack of Empathic Concern Among Support Providers - Mongrain, Myriam; Shoikhedbrod, Ariel (Frontiers in Psychiatry, 2021)
Past research has shown that the interpersonal relationships of depressed individuals are often characterized by rejection rather than compassion from significant others. The goal of this research was to broaden interpersonal models of depression by investigating individual differences among support providers, including disagreeableness, stigmatic beliefs about depression and empathic concern. These were examined in relation to reported interpersonal behaviours toward a significant other who was currently depressed. A cross-sectional design was used in an undergraduate (N= 312) and community sample (N= 296). Disagreeable individuals reported less compassionate and more rejecting behaviours toward depressed significant others based on an interpersonal circumplex model of social support. Serial mediation models further indicated that the associations between disagreeableness and rejecting behaviours reported by providers were mediated by stigma and lower empathic concern. The current studies shed light on how the personality, attitudes and emotions of support providers influence the level of compassion expressed towards depressed individuals.